Do Interbank Interest Rates Matter for Stock Prices at Nepal Stock Exchange? - Gurung, Rajesh (Pravaha, 2020)
This study examines an auto-regressive distributed lag (ADRL) modeling approach to develop the relationship between the stock price and interest rate in the context of Nepal, using the monthly data for the period from July 1996 to January 2019. NEPSE Index in Nepal Stock Exchange Limited is used for the stock prices and interbank interest rate released in Quarterly Economic Bulletin of Nepal Rastra Bank is used for the interest rate. The bound test for co-integration and estimated negative coefficient of long-run regression results justified by the Error Correction Mechanisms (ECM) establishes a valid negative long-run association between the INTEREST and PRICE. This suggests important considerations for policies towards an interest rate stabilization for the stock price stability and further development of the stock market in Nepal.